2022
DOI: 10.3389/fenvs.2022.891092
|View full text |Cite
|
Sign up to set email alerts
|

Pollution Characteristics, Sources, and Health Risk Assessment of Heavy Metals in the Surface Soil of Lushan Scenic Area, Jiangxi Province, China

Abstract: Heavy metal pollution at tourist attractions centers has caused widespread concern. In this study, the concentration of seven heavy metals (Pb, Cu, Cr, Zn, Ni, As, and Mn) in the surface soil of the Lushan scenic area was measured, and their pollution characteristics were assessed using the Nemerow comprehensive pollution index and geo-accumulation index; further, the human non-carcinogenic and carcinogenic risks were evaluated by the U.S. Environmental Protection Agency health risk assessment model. Correlati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…The contribution of the second component (PC2) was 19.062%, in which As and Cr had high positive loadings, and the loadings of As were significantly higher than those of Cr. The study showed that Cr and As were significantly correlated with soil-forming matrices, soil-forming processes and geological activities (Zhang et al, 2022;Li W. D. et al, 2019), and the correlation between Cr and As was significant, and the contents of As in all the sample sites were much smaller than the background values of Xinjiang soils. Some studies have shown that As is significantly correlated with natural soilforming matrices or soil-forming processes, but natural leaching causes the whole As content in the surface soil to be continuously exported, which results in the topsoil As content being lower than the background value (Zhao et al, 2022;Chen et al, 2022), suggesting that PC2 is a natural background source, in addition to which the mean value of Cr is slightly greater than the background value of Xinjiang soils, and it also occupies a larger proportion in PC1, suggesting that in addition to the No.…”
Section: Principal Component Analysis (Pca) Of Heavy Metal Elements I...mentioning
confidence: 93%
See 1 more Smart Citation
“…The contribution of the second component (PC2) was 19.062%, in which As and Cr had high positive loadings, and the loadings of As were significantly higher than those of Cr. The study showed that Cr and As were significantly correlated with soil-forming matrices, soil-forming processes and geological activities (Zhang et al, 2022;Li W. D. et al, 2019), and the correlation between Cr and As was significant, and the contents of As in all the sample sites were much smaller than the background values of Xinjiang soils. Some studies have shown that As is significantly correlated with natural soilforming matrices or soil-forming processes, but natural leaching causes the whole As content in the surface soil to be continuously exported, which results in the topsoil As content being lower than the background value (Zhao et al, 2022;Chen et al, 2022), suggesting that PC2 is a natural background source, in addition to which the mean value of Cr is slightly greater than the background value of Xinjiang soils, and it also occupies a larger proportion in PC1, suggesting that in addition to the No.…”
Section: Principal Component Analysis (Pca) Of Heavy Metal Elements I...mentioning
confidence: 93%
“…Heavy metals are introduced to lakes from natural occurrences and human activities, including hydrological processes, erosion, atmospheric deposition, agricultural runoff, and industrial discharge (Merciai et al, 2014;Zhang et al, 2022;Ros et al, 2014). Most heavy metals settle in sediments, with only a minor fraction remaining dissolved in water (Liu and Dilinuer, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…As not all substances have carcinogenic risk, this study only assessed the carcinogenic risk of substances listed by the IARC 13 or the Hot Spots Unit Risk and Cancer Potency Values from OEHHA 40 . The calculation formula is as follows: where CPV is the Cancer Potency Values published by OEHHA 40 ; DD is the daily dose; and SF is the carcinogenic slope factor 41 .…”
Section: Methodsmentioning
confidence: 99%
“…The balance consists of input and output fluxes of heavy metals. For input sources of heavy metals, the direct control of them can fundamentally diminish the accumulation of heavy metals in soil and the occurrence of soil pollution [17]. The accumulation of heavy metals in soil can cause irreversible harm to the soil environment.…”
Section: Introductionmentioning
confidence: 99%